Relationship Family Health Behavior with The Frequency of Occurrence of Children Upper respiratory tract infections In Puskesmas Banyu Urip Surabaya - Anggraini, Fritria Dwi; Munjidah, Annif (Journal of Global Research in Public Health, 2018)
Upper Respiratory Tract Infection (URTI) is the most common deadly disease of children in Indonesia. The disease is still underestimated by some families and still consider as harmless disease, so that it may suffered by the children repeatedly. Most parents do not understand that this disease can cause more dangerous diseases if not immediately handled, especially when the immune system is in bad condition. The purpose of this study was to determine the relationship between family health behavior with the incidence of URI of toddlers. The type of this research was analytic observational with cross sectional approach. The population was 53 mothers with sick and healthy toddlers who visited the Puskesmas Banyu Urip Surabaya. The sample was 47 respondents which taken by simple random sampling. Independent vURTIable was family health behavior while dependent vURTIable was incident of URTI. Instruments were questionnaire and interview sheet. The data analyzed by Mann-Whitney test with significance level Î± = 0,05. The result showed that most of the respondents (61,7%) had positive behavior and most of them (59,6%) rarely suffered URTI, whereas almost half (40,4%) of respondents had children often suffered URI. Mann-Whitney test analysis results show that Ï = 0.008 <0.05 then H0 was rejected means there was relationship of family health behavior with the incidence of URTI at infants at Puskesmas Banyu Urip Surabaya